RANCANG BANGUN PENAMPIL INFORMASI KEBUN BINATANG BERBASIS KOMPUTER PERSONAL MINI - Denny Darlis; Gina Ilma Amalia (Jurnal Teknologi Informasi dan Terapan, 2019)
Conventional information systems that are installed and used in public service places such as city parks require expensive and complex systems. To streamline cost and installation time, system complexity can be simplified using a relatively inexpensive system while still providing sufficient service to the community. In this study the display boards of information prepared for zoo services managed by the city government, designed and built using a mini personal computer that is now widely available on the market. To perform its function as an information display board, some eye-catching animated videos are played back and forth as needed. From the results of the implementation and testing in actual conditions it is concluded that the information display system at the zoo using personal mini computer is more interesting for visitors with a delay time of 10.82 seconds for 8 hours of playback. This indicates that this system can work reliably enough to provide information according to the visitor's needs without interruption of time delay between video information.